Of men not mice: Bactericidal/permeability-increasing protein (BPI) expressed in human macrophages acts as a phagocytic receptor and modulates entry and replication of Gram-negative bacteria. - Arjun Balakrishnan; Markus Schnare; Dipshikha Chakravortty (Frontiers in Immunology, 2016)
Macrophages as immune cells prevent the spreading of pathogens by means of active phagocytosis and killing. We report here the presence of an anti-microbial protein, bactericidal/permeability-increasing protein (BPI) in human macrophages, which actively participates in engulfment and killing of Gram-negative pathogens. Our studies revealed increased expression of BPI in human macrophages during bacterial infection and upon stimulation with various PAMPs (Pathogen-associated molecular patterns) viz., LPS, flagellin. Further, during the course of an infection, BPI interacted with Gram- negative bacteria, resulting in enhanced phagocytosis and subsequent control of the bacterial replication. However, it was observed that bacteria which can maintain an active replicating niche (Salmonella Typhimurium) avoid the interaction with BPI during later stages of infection. On the other hand, Salmonella mutants, which cannot maintain a replicating niche, as well as Shigella flexneri, which quit the endosomal vesicle, showed interaction with BPI. These results propose an active role of BPI in Gram-negative bacterial clearance by human macrophages.